Adhesion properties of a silicon-containing calcium phosphate coating deposited by RF magnetron sputtering on a heated substrate; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 7, № 5 - Surmeneva M. A. Maria Alexandrovna; Surmenev R. A. Roman Anatolievich; Koval N. N. Nikolay Nikolaevich; Pichugin V. F. Vladimir Fyodorovich; Teresov A. D.; Ivanova A. A.; Grubova L. Yu.; Ignatov V. P. Viktor Pavlovich; Primak O.; Epple M. (2013, 2013)
Title screen